The Mapping of Internet Marketing Potential for SMEs Working on Indonesian Traditional Fabrics - Nurita, Prima; Lundia, Ixora (UI Scholars Hub, 2018)
Due to their rapid development, technology and internet are widely used in business, particularly for marketing. Internet marketing generates numerous benefits. This study illustrates and analyzes the potential of internet marketing for Small and Mendium enterprises (SMEs) working on Indonesian traditional fabrics in three regions: Palembang, Solo, and Banjarmasin. The study focuses on the extent to which SMEs working on traditional fabrics in these districts apply internet marketing, mapping the potential, and providing recommendations related to a better preparation of internet marketing for SMEs to tackle competition on a global level. This study applies post-positivist paradigm by using qualitative methods. The data are collected through in-depth interviews with SMEs and the governments in the three regions. To analyze the internet marketing applied by SMEs working on traditional fabrics, this study applies the theory of Kotler and Armstrong (2012) whose indicators are: creating/designing an effective website, carrying out online promotion, creating/participating in marketing and web community, and using email. The findings can be categorized into technical and non-technical findings. Technical findings show that SMEs in these cities have not applied internet marketing or online marketing optimally. Several SMEs in Solo already have social media and websites but the majority of SMEs in two other cities simply use social media (Instagram and Facebook), BBM, and WhatsApp as media for promotion. Non-technical findings show several important elements to develop in order to achieve successful internet marketing in SMEs, namely human resources, the role of associations, the role of the government, and the value of traditional fabrics.